فاعلية برنامج مقترح في علاج صعوبات التعلم الاجتماعية والانفعالية باستخدام الأنشطة البدنية والرياضية - خوحلي، أحلام Khuhali, Ahlam (جامعة عمار ثليجي بالأغواط - كلية العلوم الاجتماعية, 2015)
هدف هذا البحث إلى اختبار برنامج تعليمي مستند إلى نظرية "جولمان" لمعالجة صعوبات التعلم الاجتماعية والانفعالية لتلاميذ المدرسة الابتدائية. وأثر ذلك على مستوى تحصليهم وذلك من خلال استخدام الأنشطة البدنية والرياضية. وقد تم اختيار العينة عمديا والمتكونة من 20 تلميذ لديهم صعوبات تعلم اجتماعية وانفعالية حسب تقديرات المعلمين. وقسمت العينة عشوائيا إلى مجموعة ضابطة ومجموعة تجريبية. ولتحقيق أهداف البحث استخدمت الباحثة برنامج المقترح للأنشطة البدنية والرياضية والاسترخاء والذي يهدف إلى تنمية المهارات الخمس للذكاء الانفعالي (الوعي بالذات، تنظيم الذات، الدافعية، التعاطف والمهارات الاجتماعية) والمتكون من 24 حصة تعليمية. ومقياس الذكاء الانفعالي ومعدلات الفصول الدراسية. وبعد تطبيق البرنامج ومقارنة النتائج القبلية والبعدية إحصائيا باستعمال المتوسطات والانحرافات المعيارية واختبار "ت"، توصلت الباحثة إلى وجود فروق ذات دلالة إحصائية في درجات مهارات الذكاء الانفعالي ومستوى التحصيل بين المجموعتين التجريبية والضابطة ولصالح المجموعة التجريبية، وهذا ما قد يعزى إلى فاعلية البرنامج المقترح.
The purpose of this study was to design the effect of using physical and sports activities in the development of Emotional Intelligence for students with learning disabilities in primary stage, and this may had a positive improvement in academic achievement. The sample study consisted of 20 students deliberately selected and randomly distributed, into two groups: the control and experimental group. The experimental group had been imposed to motor program consisted of 24 sessions. two sessions per week. To achieve the aims of the study, the following instruments were used: The motor program: It was based on Goldman's theory of Emotional Intelligence, The IQ scale and Academic achievement test. The data were statically analyzed by using means, standards deviations and “T” test. The study has shown tow results: firstly there are differences between the means of experimental and control group in Emotional skills. These differences can be attributed to the program in favor of the experimental group. Secondly there are differences between the means of experimental and control group in levels of academic achievements. These differences can be attributed to the program in favor of the experimental group.
Keywords: البرامج التعليمية -- صعوبات التعلم -- التربية الرياضية -- الأنشطة البدنية